Caracterização reológica de soluções de hidratos de tetrahidrofurano - Coelho, Icaro (2022)
The present work discusses the results obtained from rheometry of samples of tetrahydro furan hydrates with molar concentrations above saturation (1:17). The methodological procedures were also part of the preliminary results because of the influence of the THF hydrates nucleation method in the rheological characteristics of the samples tested. The techniques used to induce the formation of THF hydrates were mechanical disturbance and subcooling, the latter responsible for experimental results with a higher degree of repeatability. The vane geometry was used for the deformation tests with the mass concen trations of THF equal to 30, 35, and 40%. The increased concentration of tetrahydrofuran in the sample showed a correlation in reducing the yield stress and shear modulus. The mass concentration of THF s equal to 40% were used to build flow curves, showing shear thinning and viscoplasticity. The main factors influencing the rheological characteristics of the hydrates were the mass concentration of THF, the shear during the formation of hydrate crystals, the subcooling temperature, and the rest time after the crystal nucleation protocol.